Mesenchymal-stem-cell-derived exosomes accelerate skeletal muscle regeneration - Nakamura, Yoshihiro; Miyaki, Shigeru; Ishitobi, Hiroyuki; Matsuyama, Sho; Nakasa, Tomoyuki; Kamei, Naosuke; Akimoto, Takayuki; Higashi, Yukihito; Ochi, Mitsuo (FEBS letters, 2015)
•Mesenchymal stem cell exosomes promoted myogenesis and angiogenesis in vitro.•Mesenchymal stem cell exosomes accelerated muscle regeneration in a mouse injury model.•Mesenchymal stem cell exosomes had low concentrations of repair-related cytokines.•Many repair-related microRNAs were identified in mesenchymal stem cell exosomes.•MicroRNA-494 in mesenchymal stem cell exosomes enhanced myogenesis and angiogenesis. Mesenchymal stem cell (MSC) transplantation is used for treatment of many diseases. The paracrine role of MSCs in tissue regeneration is attracting particular attention. We investigate the role of MSC exosomes in skeletal muscle regeneration. MSC exosomes promote myogenesis and angiogenesis in vitro, and muscle regeneration in an in vivo model of muscle injury. Although MSC exosomes had low concentrations of muscle-repair-related cytokines, a number of repair-related miRNAs were identified. This study suggests that the MSC-derived exosomes promote muscle regeneration by enhancing myogenesis and angiogenesis, which is at least in part mediated by miRNAs such as miR-494.